ASSESSMENT OF REFORMING THE HEALTH PROTECTION OF THE POPULATION OF RUSSIA IN RECENT YEARS - Данцигер, Дмитрий Григорьевич; Филимонов, Сергей Николаевич; Андриевский, Борис Павлович; Часовников, Константин Викторович (Medicine in Kuzbass, 2021)
An attempt is made to assess the reform of the health care system of the Russian population in recent years. To eliminate the existing problems, two alternative approaches are proposed: the first is the introduction of private medical services, starting from the birth of a person. However, neither society nor the state is ready for such an approach. The second approach is to restore the experience of Soviet, including military, medicine as soon as possible.
Keywords: public health and health care; protection of public health